Alcoholic’s social support network: mapping based on alcoholics anonymous actions - Helder de Pádua Lima; Violante Augusta Batista Braga; Angélica Mota Marinho (Rev Rene)
We emphasize the construction of a social support network to alcoholics as a strategy for maintaining its affective and solidary ties with their families and society. This study aims to map the alcoholic’s support network from the intersectoral actions developed by members of an Alcoholics Anonymous group (AA) located in Fortaleza — Ceará. This is a descriptive study with 20 members of the AA group. The data were produced through semi-structured interviews and analyzed in accordance with the content analysis method. The results show joint actions with other self-help groups; educational institutions, health and religious institutions, as well as the general community. The absence of passages relating to joint initiatives of the health sector with AA suggests a lack of integration between the devices so that they compose an effective network in coping with alcoholism.